2021
DOI: 10.1136/openhrt-2021-001869
|View full text |Cite
|
Sign up to set email alerts
|

High levels of interleukin-6 are associated with final infarct size and adverse clinical events in patients with STEMI

Abstract: ObjectiveInflammation has emerged as a new treatment target in patients with coronary artery disease and inflammation seems to play an important role in ischaemia/reperfusion injury that follows ST-elevation myocardial infarction (STEMI). We aimed to explore the role of acute and sustained interleukin 6 (IL-6) signalling, including soluble IL-6 receptor (IL-6R), with regard to infarct size, adverse remodelling and future cardiovascular events in patients with STEMI.MethodsWe included 269 patients with first-ti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 21 publications
0
15
0
1
Order By: Relevance
“…A few studies have been carried out to explore the correlation of some specific inflammatory cytokines with MACE risk in STEMI patients. 13 , 15 , 23 , 24 , 25 For example, one previous study indicates that the elevation of IL‐6 is correlated with high MACE risk in STEMI patients who undergo PCI therapy. 13 Another study finds the important role of VCAM‐1 in the occurrence of post‐PCI restenosis.…”
Section: Discussionmentioning
confidence: 99%
“…A few studies have been carried out to explore the correlation of some specific inflammatory cytokines with MACE risk in STEMI patients. 13 , 15 , 23 , 24 , 25 For example, one previous study indicates that the elevation of IL‐6 is correlated with high MACE risk in STEMI patients who undergo PCI therapy. 13 Another study finds the important role of VCAM‐1 in the occurrence of post‐PCI restenosis.…”
Section: Discussionmentioning
confidence: 99%
“…Mounting evidence suggests that neutrophil-to-lymphocyte ratio (NLR), platelet-to-lymphocyte ratio (PLR), and neutrophil-to-platelet ratio (NPR) might be considered as biomarkers of systemic inflammation and associated with poor clinical outcomes in various cardiovascular diseases, including acute coronary syndromes (ACS) [ 1 , 6 8 ]. Moreover, recent investigations have shown that the inflammatory status correlates with infarct size and adverse clinical outcome in ACS patients [ 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Our results were also in agreement with the results of Groot et al (2019) who show that the median baseline IL-6 level was (3.7 pg/ml) and it was increased a threefold to (10.3 pg/ml) (p<0.001) after 24 h and subsequently decreased to (1.8 pg/ml) )(p<0.001) at 2 weeks to remain stable. Furthermore, the study of Tøllefsen et al (2021) carried out on 269 individuals who had undergone STEMI revealed that circulating IL-6 levels rose from the day of admission to the first day after, and then dropped to levels lower than those at the time of admission at the 4month follow-up (p<0.001). Sun et al (2020) concluded that the pre-operative expression of IL-6 (P<0.001) was increased in restenosis patients compared with non-restenosis patients.…”
Section: Discussionmentioning
confidence: 99%